A Guide to Stoicism - Stock, St. George William Joseph, 1850- (Salt Lake City, UT : Project Gutenberg, 2005)
"A Guide to Stoicism" by St. George William Joseph Stock is a philosophical treatise written in the early 20th century. This book serves as an exploration and interpretation of Stoicism, the ancient Greek philosophy founded by Zeno of Citium, which emphasizes rationality and virtue as central tenets for achieving a good life. The text reviews the foundations and key concepts of Stoicism, including ethics, logic, and physics, aiming to present the doctrines in an accessible manner. In the book, Stock meticulously outlines the principles of Stoicism, discussing key figures such as Zeno and Chrysippus and their contributions to the philosophy. He delves into Stoic ethics, advocating the idea that virtue is the only true good and that external circumstances do not determine one$1 (Bs happiness. The author also highlights the Stoic view of the universe as a rational and orderly entity governed by divine reason (Logos), asserting that human beings should align their lives with nature and pursue wisdom. Throughout the guide, Stock emphasizes the practical applications of Stoicism, advocating for a life led by reason and virtue above all else, thereby addressing both philosophical and everyday concerns for his readers. (This is an automatically generated summary.)s
Release date is 2005-02-01
Produced by Charles Franks, Ted Garvin, S. R. Ellison and the Online Distributed Proofreading Team
Keywords: Stoics